The Effectiveness of Digital Technology Implementation in Enhancing the Competitiveness of MSMEs in the Creative Industry of Tangerang City - Prasetyo, Dwi (SKeTsa Bisnis (e-jurnal), 2025)
Introduction: The Fourth Industrial Revolution has triggered a fundamental shift in the global economic structure, significantly influencing the sustainability and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. This study aims to evaluate the effectiveness of digital technology adoption in enhancing the competitiveness of MSMEs in the creative industry sector in Tangerang City. Methods: Utilizing the Technology-Organization-Environment (TOE) framework, this research applies a quantitative approach through an evaluative survey design involving 128 MSME actors who have integrated digital systems into their business operations. Results: The findings reveal that approximately 78% of respondents reported an increase in sales ranging from 20% to 35% following digital adoption, while 64% successfully expanded their market reach to national and international levels. Moreover, digital technology implementation has proven to significantly improve operational efficiency and accelerate product innovation processes, thereby strengthening the competitive edge of MSMEs. However, several challenges remain, such as limited access to formal digital training, low levels of digital literacy, and uneven availability of digital infrastructure across regions. Conclusion: The study concludes that optimal digital technology implementation can generate substantial positive impacts on MSME performance and competitiveness, provided there is strategic support from government bodies, educational institutions, and the private sector. Strengthening multi-stakeholder collaboration and building an inclusive and sustainable digital ecosystem are key strategies for advancing MSME transformation in the digital economy era. This research offers valuable implications for policy formulation and strategic empowerment of technology-based MSMEs in Indonesia.